Domownik Workbook. A Resource for Shaping Children’s Cultural Identity in Grades I–III - Lisowska, Kinga (Paedagogia Christiana, 2025)
The cultural identity of an individual – a child – a pupil and its formation is a crucial matter in times of globalisation, cultural fusion, interaction with others, and merging into intercultural, transcultural structures. In a school setting, the children can have new, broader experiences constituting belonging to a given cultural community. In the first three grades of primary school, this is done through early childhood education and (importantly) through school religious education in the form of catechesis and the tools and textbooks used during it. It combines the cultural identity conferred in the family with the identity naturally conveyed through religion. This paper presents a qualitative analysis of the secondary source in the form of the workbook Domownik – a supplement for the family, which accompanies the school catechesis textbooks of the Catholic Church in the first educational stage. It was concluded that the workbook includes features leading to ethnos, which is recognised as a determinant for cultural identity formation. These features guide the pupil towards the knowledge and education of language (linguistic codes), customs (communal celebrations), history (collective memory) and being rooted in religion. They also mobilise them to explore the values and principles characteristic of the Catholic Church community in Poland and to open up to the experiences that make up the structure of an individual’s identity embedded in the reality of affiliation and identification with a particular social community. Domownik is a tool for working with the pupil through collaboration with his/her most immediate cultural group – the family. It is designed to be used as an optional extra task for children in grades I–III in their home environment. In school, on the other hand, it is sometimes used alongside – on a par with – instead of the textbook.